(untitled) (Western European Journal of Medicine and Medical Science, 2025)
The high incidence of acute intestinal infections (AII) among children, second only to respiratory pathology, the frequency of adverse disease outcomes, and the low level of laboratory diagnosis have highlighted the medical and social significance of research aimed at studying this problem.